PENGARUH TEKNIK RELAKSASI GENGGAM JARI TERHADAP PENURUNAN INTENSITAS NYERI PADA IBU POST SECTIO CAESAREA (Jurnal Kesehatan Siliwangi, 2022)
One of the way to decrease the death rate of mother and infant during childbirth is through sectio caesarea. SC operation generates pain from the incision site. Patients will feel severe pain on the first two hours on average after procedure because the effects of anesthetic drugs are slowly decreasing. The efforts to overcome pains in mothers who undergo SC procedure are both pharmacological and non-pharmacological. Non pharmacological methods are relaxations, breathing technique, movements and position changes, massage, acupressure, hot-and-cold therapy, hypnobirthing, music and tens. One of the non-pharmacological way to reduce pain is the hand-held relaxation technique. The hand-held relaxation technique is an easy way to control emotions and develop emotional intelligence. This research aims to determine the effect of the hand-held technique on the reduction of pain intensity in post sectio caesarea mother. The article search was carried out on October 2nd 2021 using Google scholar database published in the last 5 years, previously screened then reviewed critically. The result of the case study after the hand-held technique in Mrs. R, there is a decrease in the intensity of pain from scale 6 to scale 3.